2016
DOI: 10.4269/ajtmh.15-0549
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Rhabdomyolysis After Protobothrops flavoviridis Bite: A Retrospective Survey of 86 Patients in a Tertiary Care Center

Abstract: Abstract. Acute kidney injury (AKI) is the main cause of death for victims of hematoxic snakebites. A few studies have described improvement in AKI rates in snakebite cases, but the reasons for the improvement have not been investigated. Eighty-six patients with Protobothrops flavoviridis bites admitted to a single center from January 2003 through March 2014 were included in the study. Clinical variables, including age, sex, blood pressure (BP), and serum creatinine (S-Cre), on admission were compared between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Consistent with the extreme variation in their venoms, Protobothrops species are highly variable in morphology and ecological niche occupied, ranging from heavily built terrestrial species (eg P. mangshanensis) to gracile semi-arboreal species (eg P. flavoviridis). While the venom variation is suggestive of this feature being a driver in their adaptive radiation, it is also indicative of the potential to produce differential clinical effects, in that while haemorrhagic shock may be produced by all (Chen et al, 2009;Nishimura et al, 2016), the underlying mechanics may be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the extreme variation in their venoms, Protobothrops species are highly variable in morphology and ecological niche occupied, ranging from heavily built terrestrial species (eg P. mangshanensis) to gracile semi-arboreal species (eg P. flavoviridis). While the venom variation is suggestive of this feature being a driver in their adaptive radiation, it is also indicative of the potential to produce differential clinical effects, in that while haemorrhagic shock may be produced by all (Chen et al, 2009;Nishimura et al, 2016), the underlying mechanics may be different.…”
Section: Discussionmentioning
confidence: 99%
“…The wide-ranging Asian pit viper genus Protobothrops occupies the islands of Japan, mainland China and islands off China, with the occupation of diverse ecological niches mirrored by diverse morphology. Protobothrops bites are known for potent haemorrhagic shock effects in prey and human bite victims (Chen et al, 2009;Nishimura et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…43 Recently, Nishimura et al reported 86 cases of habu bites from 2003 to 2014 in Amami Ohshima, a known habu habitat in Kagoshima prefecture. 44 Good clinical outcomes were reported in this area, with 97.7% (84/86 patients) receiving antivenom therapy and a mortality rate of only 1.1% (1/86 cases). In contrast, the mortality rate reported in the same area in 1978 was 10%.…”
Section: Habu (Protobothrops Flavoviridis) Bitesmentioning
confidence: 89%
“…Consistent with the extreme variation in their venoms, Protobothrops species are highly variable in morphology and ecological niche occupied, ranging from heavily built terrestrial species (eg P. mangshanensis) to gracile semi-arboreal species (eg P. flavoviridis). While the venom variation is suggestive of this feature being a driver in their adaptive radiation, it is also indicative of the potential to produce differential clinical effects, in that while haemorrhagic shock may be produced by all Nishimura et al, 2016), the underlying mechanics may be different.…”
Section: Platelet Agglutination and Inhibitionmentioning
confidence: 99%
“…The wide-ranging Asian pit viper genus Protobothrops occupies the islands of Japan, mainland China and islands off China. Protobothrops bites are known for potent haemorrhagic shock effects in prey and human bite victims Nishimura et al, 2016). Target sites include impeding primary haemostasis by disruption along the cascade from the blockage of platelet aggregation through to inhibiting clot formation due to the unnatural cleavage of fibrinogen (Collet et al, 2000;Kolev and Longstaff, 2016;Longstaff and Kolev, 2015;Mosesson, 2005).…”
Section: Introductionmentioning
confidence: 99%